On the lamb - Kashian, Tina (Kashian, Tina. Kebab Kitchen mystery., 2020)
When Melanie and Lucy attend a beach bonfire, a local landlord is found dead after apparently choking on a piece of salt water taffy. Melanie, who was known to have a contentious relationship with the victim, is quickly skewered as the prime suspect. But Lucy is determined to prove her friend's innocence before the real killer coasts free. --